Portal vein variants associated with right hepatectomy: An analysis of abdominal CT angiography with 3D reconstruction. Issue 3 (7th January 2019) - Clipet, Fabien; Rebibo, Lionel; Dembinski, Jeanne; Yzet, Thierry; Vilgrain, Valérie; Regimbeau, Jean‐Marc
Abstract : Glissonian approach has been described as a selective vascular clamping procedure during hepatectomy based on external anatomical landmarks. Anatomical variations of the right Glissonian pedicle have been identified with an increased risk of clamping failure during Glissonian approach. The objective of this study was to characterize the anatomical variations of the right Glissonian pedicle at risk of clamping failure during right hepatectomy. This was a retrospective analysis of abdominal multiphasic CT and routine 3D reconstruction (n = 346). Anatomical variations at risk of clamping failure were Types 1 to 3 (Madoff's classification) and an angle of less than 50° between the portal vein and the left portal vein. Primary objective was the risk of right Glissonian pedicle clamping failure. Secondary objectives were the rate of normal anatomy, the rate of variations, and the rate of incomplete or extended clamping. Normal anatomy was found in 245 patients (71%). Anatomical variations were as follows: Type 1: 11%, Type 2: 17%, Type 3: 0.8%, Type 4: 0%. Angle variation less than 50° was observed in 4.5%. The risk of selective clamping failure was 34%. Extension of clamping was observed in 16%, while incomplete clamping was observed in 17.8%. Failure of right Glissonian pedicle clamping was predictable in 34% of cases while 71% of patients presented normal portal vein anatomy. Clin. Anat. 32:328–336, 2019. © 2018 Wiley Periodicals, Inc.